Challenges Perceived by Indonesian ESP Teachers in Post-Pandemic Era: A Survey from a Higher Education Institution - Andri Suherman; Lalu Kertawijaya (Scope : Journal of English Language Teaching, 2023)
This study examines challenges experienced by Indonesian ESP teachers in face-to-face education system, and possible solutions they have deployed to tackle the challenges. An online survey was employed to discover challenges the ESP teachers perceived, which was then quantitatively analysed using SPSS software. Besides, semi-structure interviews were carried out to explore solutions the ESP teachers had deployed to resolve the challenges, which was then qualitatively analysed using coding system. The findings show that the ESP teachers are dealing with five major challenges with inadequate teaching material being the most challenging (M=3.15, SD=0.88) and unsupported institution system being the least challenging (M=2.34, SD=0.62). To tackle the challenges, the teachers employ several techniques such as adapting ready-made materials, collaborating with specific-subject teachers, and participating in relevant trainings, and asking for IT experts’ assistance. As the findings reveal, this study provides us with pedagogical implications such as the need of relevant trainings and adequate textbooks for ESP teachers and placement tests for ESP students. Some limitations and suggestions for future studies are also presented.